Intangible Capital and Growth Essays on Labor Productivity, Monetary Economics, and Political Economy, Vol. 1 - Roth, Felix (Contributions to Economics, 2022)
For several decades now, advanced economies across the globe have been undergoing a process of rapid transformation towards becoming knowledge economies. It is now widely recognized that intangible capital has been a crucial element in the growth performance of these economies and their firms. In the author's view, "intangible capital" serves as the most appropriate umbrella term for capturing several dimensions of capital that are not tangible in nature but are nevertheless fundamentally important for growth. The term encompasses investments in education (human capital) and in informal (social capital) and formal (rule of law) institutions by the public sector and households, as well as investments by businesses aimed at enhancing their knowledge base, such as software, innovative property, and economic competencies. Intangible Capital and Growth is the first of two open access volumes presenting a selection of the author's essays on Labor Productivity, Monetary Economics, and the Political Economy, which represent the first part of his habilitation in economics. This first volume brings together eight of the author's essays, selected to provide an overview of the evolution of his research on intangible capital and growth. .